Nuclear receptors and skeletal muscle fiber type - Mizunoya, W. (The Journal of Physical Fitness and Sports Medicine, 2015)
The contractile and metabolic properties of skeletal muscle depend on muscle fiber type composition. There are two major fiber types: type 1 fibers (slow-twitch oxidative) and type 2 fibers (fast-twitch glycolytic). Muscle fiber type is a critical physiological property that affects sports performance and metabolic ability. To date, natural food components have not been regarded as regulators of skeletal muscle fiber type. Meanwhile, in the present century, it has been revealed that several nuclear receptors (NRs) and their cofactors affect skeletal muscle fiber type independently from muscular contraction. Interestingly, many compounds from natural food sources have been identified as NR ligands. These facts indicate the possibility of the regulation of muscle fiber type by food components. In this review, we present an overview of the current knowledge of the role of NRs and their cofactors in skeletal muscle fiber type and discuss the perspective of muscle fiber type regulation by food components via NR.